Peran Doa dalam Kehidupan Keluarga Kristiani sebagai Ecclesia Domestica - Suwito, Benny (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
Prayer is an integral part of family life. It helps family to face many problems in society even as the vital cell of society, family needs more prayers. Christian Families, as “ecclesia domestica”, obtain their identity from the Church, the bride of Christ. They have duty to pray because prayer unites them to Christ, the centre of family. Moreover, Christian families as “ecclesia domestica” have the same mission as the Church. Christian families need prayer in their daily lives because, identical to the Church, they pray together as community to invoke the help of God for their families lives. Thus, based on this context, this paper wants to explain how prayers in Christian Families have a significant effect in assisting and protecting them from dangerous ideologies such as secularism that break families in modern society.